Logistic regression analysis of pregnancy outcome and EFI score of infertile patients with ovarian endometriosis cyst after staged oral administration of traditional Chinese medicine - Bo, Yali; Peng, Shaochan; Su, Jiawen; Ye, Dunmin (Frontiers in Endocrinology, 2025)
BackgroundOvarian endometriosis cysts are associated with infertility, and recent research increasingly focuses on improving pregnancy outcomes. Traditional Chinese medicine (TCM) has long been used for gynecological issues, yet the impact of staged TCM administration on pregnancy outcomes and Endometriosis Fertility Index (EFI) scores in infertile patients remains underexplored.ObjectiveThis study aims to evaluate the effects of staged TCM administration on pregnancy outcomes and EFI scores in patients with ovarian endometriosis cysts.MethodA retrospective analysis of 150 infertile patients treated with staged TCM administration was conducted. Patients received Formula I before ovulation and Formula II post-ovulation, with the cohort split into pregnancy (n=91) and non-pregnancy groups (n=49). All patients underwent laparoscopic surgery prior to TCM treatment. Logistic regression and ROC analysis were used to assess pregnancy predictors.ResultsSignificant differences in age, infertility type, infertility duration, r-AFS stage, cyst diameter, and EFI score (P<0.05) were found. Age, secondary infertility, infertility duration (≥3 years), advanced r-AFS stage, cyst diameter (≥3cm), and EFI score (<7) were key risk factors. The EFI score’s AUC for predicting pregnancy was 0.731 (95%CI, 0.617-0.844), with 72.58% sensitivity and 75.83% specificity. No significant difference in follow-up duration was observed between the groups.ConclusionAge, secondary infertility, infertility duration (≥ 3 years), r-AFS stage (stages III and IV), cyst diameter (≥ 3cm), and EFI score (< 7) were identified as risk factors for infertility in patients with ovarian endometriosis following a two-phase staged oral administration of traditional Chinese medicine. Among these factors, the EFI score can serve as a crucial evaluation index for postoperative pregnancy, assessing the likelihood of pregnancy and predicting patient prognosis.